A case report of patellar fracture treated by percutaneous strong suture technique. (September 2021) - Hada, Shinnosuke; Ishijima, Muneaki; Tomita, Yoshimasa
Abstract: Tension-band wiring with metal such as Kirshner wire or soft steel wire is commonly used for the treatment of patellar fractures. In recent years, metal-free surgery using a strong suture with high breaking strength has been reported to have excellent outcomes. We report a case of patellar fracture treated with a minimally invasive percutaneous strong suture. The patient is a 57-year-old salesman who fell at work, hit his knee, and came to our hospital complaining of pain. His range of motion was −15° in extension and 60° in flexion. His X-ray results showed a transverse fracture of the right patella with a 3-mm displacement, and surgery was performed 7 days post-injury. A small incision of 1 cm was made distally and proximally on the patella. Two 2.0-mm perforated K-wires were inserted from distal to proximal sides, and the wire was pulled out proximally with FiberWire® No. 2. The distal end of the FiberWire was pulled through the proximal incision via the anterior surface of the patella and finally fastened. The procedure was completed in 21 min. The patient did not use a brace since the operation day and was not restricted in terms of load or range of motion. He was able to walk without any assistance after 10 days and returned to driving and office work 14 days postoperatively. At the final follow-up, no symptoms of skin irritation were detected, and the patient did not require suture removal. Highlights: Patella fractures are operated with strong sutures such as fiberwire. Strong suture technique has the same or higher strength as soft steel wire tension band. Less complications such as subcutaneous pain due to the non-metal method. Strong suture technique can be performed percutaneously. Strong suture technique is minimally invasive surgery for patellar fractures.